PENYULUHAN KESEHATAN TELINGA SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT DI BANJAR JAGATAMU, DESA MELILING, TABANAN - Ida Ayu Mirah Agung; I Gusti Ayu Prema Yani Sidemen; Anak Agung Istri Aiswarya Novitrianti (Bajang Institute, 2025)
The ear is one of the five main senses in the human body. The ear has a primary function as a sense of hearing which is very necessary in facilitating communication between humans. Ear and hearing diseases are very often missed and overlooked. Patients rarely go for treatment because they consider it trivial or are even unaware of the disease in their ears or hearing, unless their daily activities are disrupted or they experience communication disorders. The Indonesian government through the National Strategic Plan (RENSTRANAS) recorded that the most common cause of morbidity in outer ear disease is cerumen block/cerumen obsturans at 4.6%, and middle ear disease is Chronic Suppurative Otitis Media (CSOM) of the benign type at 3% (Ministry of Health of the Republic of Indonesia, 2019). The World Health Organization (WHO) states that more than 5% of the world's population has hearing loss (432 million adults and 34 million children) (WHO, 2021). This outreach event is focused on supporting the Sound Hearing 2030 program, where one of the main focuses is to eradicate hearing loss due to cerumen block/cerumen obsturans. The counseling was held in Banjar Jagatamu, Meliling Village, Kerambitan - Tabanan, by lecturers from the Faculty of Medicine, Mahasaraswati University, Denpasar, involving local residents